Exploring the Associations between Reading Skills and Eye Movements in Elementary Children's Silent Sentence Reading. Issue 1 (7th February 2022) - Lee, Sungyoon; Woltering, Steven; Prickett, Christopher; Shi, Qinxin; Sun, Huilin; Thompson, Julie L.
Abstract: The purpose of this study was to investigate the associations between elementary students' reading skills and their online reading (i.e., real-time reading) behaviors during silent sentence processing. Thirty-five students participated in this study and their eye movements were recorded during sentence reading tasks. The effects of students' reading skills measured by traditional standardized measures were investigated for widely-used eye tracking measures such as first fixation duration, gaze duration, regression path duration, total duration, word skipping, fixation count, and regression frequency. The eye tracking measures were chosen to represent early/late cognitive processes and temporal/spatial gaze behaviors. Linear mixed-effects regression analyses revealed that children's performances in reading skills predict most of the eye tracking measures.